(untitled) (The Review of Diabetic Studies, 2025)
Objective: This study investigates the effects of occupational burnout on job performance and satisfaction among healthcare workers in the Ministry of Health, Jeddah. Methods: We conducted a cross-sectional study among 702 healthcare workers currently serving at the Ministry of Health (MOH), Jeddah. Participants were recruited through a non-probability consecutive sampling technique and assessed on demographics, job characteristics, working conditions, and absenteeism. Burnout was measured using a validated Maslach Burnout Inventory (MBI) tool, evaluating emotional exhaustion, depersonalization, and personal accomplishment. Job satisfaction was assessed using 21 Likert scale items (strongly agree to strongly disagree) across workload, pressure, value conflicts, and reinforcement. Results: Among 702 healthcare workers, the majority were male (76.5%), Saudi nationals (99.6%), married (81.6%), and aged 40-49 years (46.5%). Mean burnout scores indicated moderate emotional exhaustion (5.70 ± 5.18) and personal accomplishment (14.64 ± 5.89), with low depersonalization (1.39 ± 2.95). The overall mean burnout score was 18.44 ± 9.07. The total job satisfaction score was 66.61 ± 14.87, indicating moderate overall satisfaction. Job satisfaction positively correlated with work power (r=0.741; p<0.001), and positive enforcement (r=0.833; p<0.001), while it is negatively correlated with work pressure (r=-0.751; p<0.001), conflict of values (r=-0.675; p<0.001), and burnout (r=0.295; p=0.001). Conclusion: There is bi-directional interaction between burnout, job satisfaction and factors reflecting performance of healthcare workers. Targeted interventions to reduce burnout, such as improving workflow organization and enhancing workplace support, are essential to sustain employee well-being and satisfaction.